Long Noncoding RNA BC032913 as a Novel Therapeutic Target for Colorectal Cancer that Suppresses Metastasis by Upregulating TIMP3 - Jiaxin Lin; Xin Tan; Lin Qiu; Long Huang; Yi Zhou; Zhizhong Pan; Ranyi Liu; Shuai Chen; Rong Geng; Jiangxue Wu; Wenlin Huang (Elsevier, 2017)
Summary: Long noncoding RNAs (lncRNAs) have been shown to play critical roles in the biology of various cancers. However, their expression patterns and biological functions in human colorectal cancer (CRC) remain largely unknown. The aim of this study was to explore lncRNA profiles in CRC and investigate key lncRNAs involved in CRC tumorigenesis and progression. The microarray data of six CRC and matched non-cancerous tissues revealed distinct lncRNA profiles, including 899 upregulated and 1,646 downregulated lncRNAs (p < 0.05, fold change > 2.0). Furthermore, we found that the lncRNA BC032913 was generally underexpressed in 115 CRC samples compared with normal tissues. Reduced BC032913 levels were significantly associated with an advanced tumor, lymph nodes, distant metastasis (TNM) stage and a higher risk of lymph node and distant metastases. BC032913 downregulation indicated poor overall survival in CRC patients. Moreover, BC032913 enhanced the mRNA and protein expression of TIMP3 and inhibited Wnt/β-catenin pathway activity, thus suppressing CRC metastasis in vitro and in vivo. Collectively, the obtained data show that BC032913 plays an inhibitory role in CRC aggression by upregulating TIMP3, followed by inactivation of the Wnt/β-catenin pathway. Our findings indicate that the novel lncRNA BC032913 could serve as a novel prognostic marker and effective therapeutic target for CRC. Keywords: colorectal cancer metastasis, lncRNA BC032913, TIMP3